Analisis Dengan Metode Klasifikasi Menggunakan Decission Tree Untuk Memprediksi Penentuan Resiko kredit Bank - Afdhal Syafnur (STMIK Royal, 2017)
Abstract: There are several facilities in distributing funds to the customer which is owned by Bank Syariah Bukopin. One of them is Kredit Pemilikan Rumah / Housing Loan (mortgage), so far the bank when provides mortgages to customers still uses risk prediction manually in giving credit to customers which is taking up a lot of time and energy especially when the customer reports is further analyzed by the Bank. One technique that can help in predicting the Bank's credit risk determination is Decision Tree which is a technique that is a part of Data Mining techniques to take a decision in the form of a tree. With Decision Tree techniques, it is expected to help the bank to allow faster and easier in predicting the data and getting a conclusion from existing data. One of the ways to predict the data is using Dtreg software. This software only uses data that is in the format of